2022
DOI: 10.1002/tcr.202200021
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Synthesis of CoCO3 with Controlled Morphologies

Abstract: Cobalt carbonates and derivatives represent most promising cost-effective materials for energy storage, conversion and upgrading. Morphology determines the performances, as size, shape and electronic configuration are key factors for tunable properties in the area of batteries, catalysis, magnetics and plasmonics. However, there is lack of insights in literature on morphological control of cobalt carbonates during hydrothermal and solvothermal conditions. Therefore, this review provides detailed discussion on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(219 reference statements)
0
0
0
Order By: Relevance
“…Spherocobaltite occurs all over the world [46] and is widely synthesized for technical purposes (e.g., [47]). Previously, it was found that the reaction temperature (typically >> 100 • C [47,48]) is a key factor in the formation of the CoCO 3 crystals, as the reaction rate decreases with the reaction temperature decreasing, thus decreasing the nucleation rate and growth rate (e.g., [49]). So, probably no spherocobaltite can be obtained at low (<30 • C) temperatures.…”
Section: The Effect Of Temperaturementioning
confidence: 99%
“…Spherocobaltite occurs all over the world [46] and is widely synthesized for technical purposes (e.g., [47]). Previously, it was found that the reaction temperature (typically >> 100 • C [47,48]) is a key factor in the formation of the CoCO 3 crystals, as the reaction rate decreases with the reaction temperature decreasing, thus decreasing the nucleation rate and growth rate (e.g., [49]). So, probably no spherocobaltite can be obtained at low (<30 • C) temperatures.…”
Section: The Effect Of Temperaturementioning
confidence: 99%